DEVELOPMENT OF PHYSICS STUDENT WORK SHEET (SWS) TO BUILD SCIENCE PROCESS SKILL VALUED CONSERVATION (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
Student Work Sheet (SWS) which contains only a summary of the material and exercises does not train students to investigate and develop conservation values. The research objective is to also prepared worksheets guided inquiry that can enhance science process skills, understanding of the concept and develop conservation value. Elements of inquiry and conservation value generated through work instructions and investigation. The study was performed by using one group pretest-posttest design. Research procedures include observation and identification of weaknesses worksheets, planning, early product development and initial field trials. Feasibility and legibility using questionnaires and tests hiatus. The value of understanding the concept derived from the pretest-posttest. Data science process skills gained from the observation during the lesson. Conservation values obtained from the students' self-assessment questionnaire and assessment questionnaire between friends. The analysis showed guided inquiry SWS easy to understand and very fit for use as teaching materials. Test gain showed guided inquiry SWS can enhance science process skills and conceptual understanding, and can be used as a medium to develop conservation value.LKS yang hanya berisi ringkasan materi dan latihan soal tidak melatih siswa melakukan penyelidikan dan mengembangkan nilai konservasi. Tujuan penelitian RD ini adalah menyususn LKS yang mampu meningkatkan keterampilan proses sains, pemahaman konsep dan nilai konservasi. Nilai konservasi dimunculkan melalui petunjuk kerja dan kegiatan penyelidikan.Ujicoba menggunakanOne Group Pretest-Posttest Design. Prosedur penelitian meliputi observasi dan identifikasi kelemahan LKS, perencanaan, pengembangan produk awal dan uji coba lapangan awal. Uji kelayakan dan keterbacaan menggunakan angket dan tes rumpang. Nilai pemahaman konsep diperoleh dari pretest-posttest. Data keterampilan proses sains diperoleh dari hasil observasi selama pembelajaran. Nilai konservasi siswa diperoleh dari hasil angket penilaian diri dan angket penilaian antarteman. Hasil analisis menunjukkan LKS mudah dipahami dan sangat layak digunakan sebagai bahan ajar. Uji gain menunjukkan LKS dapat meningkatkan keterampilan proses sains dan pemahaman konsep, sertadapat digunakan sebagai media untuk mengembangkan nilai konservasi.